1995
DOI: 10.1021/bi00002a031
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Nuclear GTP-Binding Protein Ran with Its Regulatory Proteins RCC1 and RanGAP1

Abstract: The guanine nucleotide dissociation and GTPase reactions of Ran, a Ras-related nuclear protein, have been investigated using different fluorescence techniques to determine how these reactions are stimulated by the guanine nucleotide exchange factor RCC1 and the other regulatory protein, RanGAP1 (GTPase-activating protein). The intrinsic GTPase of Ran is one-tenth of the rate of p21ras and is even lower in the Ran(Q69L) mutant. Under saturating conditions the rate constant for the RanGAP1 stimulated GTPase reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
310
1
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 329 publications
(341 citation statements)
references
References 66 publications
20
310
1
10
Order By: Relevance
“…(22), we examined the effect of Kap95p on the binding of guanine nucleotides to Gsp1p. First, we examined the effect of Kap95p on the Gsp1p-GDP dissociation by monitoring the loss of Gsp1p-bound ]GDP was stable over 60 min, whereas it was strongly destabilized in the presence of EDTA, consistent with previous observations (3,23 . Ran has a 10-fold higher affinity for GDP compared with GTP (23); therefore, this result suggested that upon formation of the Kap95p⅐Gsp1p complex, Gsp1p adopted a conformational state that favored the binding of GTP over GDP.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…(22), we examined the effect of Kap95p on the binding of guanine nucleotides to Gsp1p. First, we examined the effect of Kap95p on the Gsp1p-GDP dissociation by monitoring the loss of Gsp1p-bound ]GDP was stable over 60 min, whereas it was strongly destabilized in the presence of EDTA, consistent with previous observations (3,23 . Ran has a 10-fold higher affinity for GDP compared with GTP (23); therefore, this result suggested that upon formation of the Kap95p⅐Gsp1p complex, Gsp1p adopted a conformational state that favored the binding of GTP over GDP.…”
Section: Methodssupporting
confidence: 75%
“…1). However, although RCC1 has almost no preference for the nucleotide state of Ran and catalyzes the nucleotide exchange in both directions (23), nucleotide exchange by Kap95p (importin-␤) is unidirectional because of the stable association of Kap95p (importin-␤) with Gsp1p-GTP (Ran-GTP). The stability of the nucleotide-free Ran⅐Kap95p complex, demonstrated by the inability of Kap60p to dissociate it (Fig.…”
Section: Kap95p (Importin-␤) As a Nucleotide Exchange Factor; Comparimentioning
confidence: 99%
“…Ran acetylation only marginally affects the intrinsic nucleotide hydrolysis rate. The intrinsic GTP hydrolysis rate of Ran is very slow (5.4 × 10 −5 s −1 at 37°C) and would not be of biological significance if not 10 5 -fold (2.1 s −1 at 25°C) accelerated by RanGAP (31). We speculated that acetylation of lysines in the switch regions (K37 R and K71 R ) modulates intrinsic and/or RanGAP-mediated GTP hydrolysis.…”
Section: Ran Acetylation Impairs the Rcc1-catalyzed Nucleotide Exchangementioning
confidence: 98%
“…Moreover, asymmetric distribution of Ran, RCC1, RanGAP1 and RanBP1 [46][47][48] results in a steep RanGTP gradient across the nuclear envelope; High RanGTP concentration in the nucleus, whereas high RanGDP concentration in the cytoplasm [30]. Furthermore, Ran is required directly for nuclear export rather than for re-import of potential export mediators [30].…”
Section: Failure Of Exp6 Binding To Rangtp Both In the Replicative Anmentioning
confidence: 99%